1992
DOI: 10.1126/science.258.5088.1617
|View full text |Cite
|
Sign up to set email alerts
|

Paleoearthquakes in the Puget Sound Region Recorded in Sediments from Lake Washington, U.S.A

Abstract: Holocene sediments in Lake Washington contain a series of turbidites that were episodically deposited throughout the lake. The magnetic signatures of these terrigenous layers are temporally and areally correlatable. Large earthquakes appear to have triggered slumping on the steep basin walls and landslides in the drainage area, resulting in turbidite deposition. One prominent turbidite appears to have been deposited about 1100 years ago as the result of a large earthquake. Downcore susceptibility patterns sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Liquefaction and fluidization can be induced by many natural processes, including overloading, unequal loading, wave-induced cyclical and/or impulsive stresses, sudden changes in groundwater level, and earthquakes (Owen, 1987(Owen, , 1996. Soft-sediment deformation structures related to seismically-induced liquefaction or fluidization (seismites, sensu Seilacher, 1969sensu Seilacher, , 1984sensu Seilacher, , 1991 have been analysed by many authors and reported from all sedimentary environments, but they seem to be particularly common in lacustrine successions (Sims, 1973(Sims, , 1975(Sims, , 1976Ben-Menahem, 1976;Hesse and Reading, 1978;Sedimentary Geology 196 (2007) 31 -45 www.elsevier.com/locate/sedgeo Hempton and Dewey, 1983;Seilacher, 1984;Plint, 1985;El-Isa and Mustafa, 1986;Anand and Jain, 1987;Davenport and Ringrose, 1987;Scott and Price, 1988;Ringrose, 1989;Beck et al, 1992;Karlin and Abella, 1992;Van Loon et al, 1995;Beck et al, 1996;Alfaro et al, 1997;Lignier et al, 1998;Malkawi and Alawneh, 2000;Rodríguez Pascua et al, 2000;Becker et al, 2002;Leroy et al, 2002;Bowman et al, 2004;Migowski et al, 2004;Weidlich and Bernecker, 2004;Schnellmann et al, 2005). Moreover, some homogeneous silty beds in lacustrine environments have been interpreted as seismites (Doig, 1986(Doig, , 1990Shilts and...…”
Section: Introductionmentioning
confidence: 96%
“…Liquefaction and fluidization can be induced by many natural processes, including overloading, unequal loading, wave-induced cyclical and/or impulsive stresses, sudden changes in groundwater level, and earthquakes (Owen, 1987(Owen, , 1996. Soft-sediment deformation structures related to seismically-induced liquefaction or fluidization (seismites, sensu Seilacher, 1969sensu Seilacher, , 1984sensu Seilacher, , 1991 have been analysed by many authors and reported from all sedimentary environments, but they seem to be particularly common in lacustrine successions (Sims, 1973(Sims, , 1975(Sims, , 1976Ben-Menahem, 1976;Hesse and Reading, 1978;Sedimentary Geology 196 (2007) 31 -45 www.elsevier.com/locate/sedgeo Hempton and Dewey, 1983;Seilacher, 1984;Plint, 1985;El-Isa and Mustafa, 1986;Anand and Jain, 1987;Davenport and Ringrose, 1987;Scott and Price, 1988;Ringrose, 1989;Beck et al, 1992;Karlin and Abella, 1992;Van Loon et al, 1995;Beck et al, 1996;Alfaro et al, 1997;Lignier et al, 1998;Malkawi and Alawneh, 2000;Rodríguez Pascua et al, 2000;Becker et al, 2002;Leroy et al, 2002;Bowman et al, 2004;Migowski et al, 2004;Weidlich and Bernecker, 2004;Schnellmann et al, 2005). Moreover, some homogeneous silty beds in lacustrine environments have been interpreted as seismites (Doig, 1986(Doig, , 1990Shilts and...…”
Section: Introductionmentioning
confidence: 96%
“…Most of them describe deformed beds (load structures, clastic dykes, sand blows, etc.) in lacustrine successions of different ages cropping out in tectonically-active basins Alsop and Marco, 2013;Ben-Menahem, 1976;Calvo et al, 1998;Davenport and Ringrose, 1987;El-Isa and Mustafa, 1986;Gibert et al, 2005;Hempton and Dewey, 1983;Hesse and Reading, 1978;Karlin and Abella, 1992;Moretti and Ronchi, 2011;Moretti and Sabato, 2007;Ringrose, 1989a, b;Rodríguez-Pascua et al, 2000;Weidlich and Bernecker, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are complementary; the onshore record provides temporal precision for the most recent events by using radiocarbon dating, coral chronology, and dendrochronology (tree-ring dating), whereas the turbidite record extends farther back in time, at least 10,000 years in Cascadia, which is long enough to encompass many earthquake cycles. In recent years, turbidite paleoseismology has been attempted in Cascadia (Adams, 1990;others, 2003a,b, 2008;Nelson, C.H., and others, 1996;Nelson, C.H., and Goldfinger, 1999;Blais-Stevens and Clague, 2001), Puget Sound (Karlin and Abella, 1992;Karlin and others, 2004), Japan (Inouchi and others, 1996), the Mediterranean (Anastasakis and Piper, 1991;Kastens, 1984;Nelson, C.H., and others, 1995b), the Dead Sea (Niemi and Ben-Avraham, 1994), northern California (Field and others, 1982;Field, 1984;Garfield and others, 1994;others, 2007a, 2008), Lake Lucerne (Schnellmann and others, 2002), Taiwan (Huh and others, 2006), the southwest Iberian margin (Gràcia and others, 2010), the Chile margin (Blumberg and others, 2008;Völker and others, 2008), the Marmara Sea (McHugh and others, 2006;Beck and others, 2007), the Sunda margin (Patton and others, 2007(Patton and others, , 2009(Patton and others, , 2010, and the Arctic ocean (Grantz and others, 1996). Results from these studies suggest the turbidite paleoseismologic technique is evolving as a useful tool for seismotectonics.…”
Section: Significance Of Turbidite Paleoseismologymentioning
confidence: 99%